2017
DOI: 10.1371/journal.pone.0182485
|View full text |Cite
|
Sign up to set email alerts
|

Safe delivery care practices in western Nepal: Does women’s autonomy influence the utilization of skilled care at birth?

Abstract: Despite various efforts to increase the utilization of skilled birth attendants (SBA), nearly two-thirds of deliveries take place at home without the assistance of SBAs in Nepal. We hypothesized that the ability of women to take decisions about their own lives—women’s autonomy—plays an important part in birth choices. To know this, we conducted a community-based cross-sectional study for assessing women’s autonomy and utilization of safe delivery care service in Kapilvastu district of Nepal from June to Octobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 25 publications
5
20
0
Order By: Relevance
“…This study found significant relationships between women autonomy, antenatal care visits and health facility delivery. The findings of this study are consistent with the findings of (Asweto et al, 2014;Baral et al, 2010;Bhandari et al, 2017;Deo et al, 2015;Fawole and Adeoye, 2015;Woldemicael, 2007b), who found that maternal healthcare utilisation is influenced by women autonomy. Also, the findings of this study are in agreement with the findings of Sharma et al, (2007) where it was stated that women with greater autonomy irrespective of physical and financial resources are able to manage their own children's health care and make fertility decisions too.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This study found significant relationships between women autonomy, antenatal care visits and health facility delivery. The findings of this study are consistent with the findings of (Asweto et al, 2014;Baral et al, 2010;Bhandari et al, 2017;Deo et al, 2015;Fawole and Adeoye, 2015;Woldemicael, 2007b), who found that maternal healthcare utilisation is influenced by women autonomy. Also, the findings of this study are in agreement with the findings of Sharma et al, (2007) where it was stated that women with greater autonomy irrespective of physical and financial resources are able to manage their own children's health care and make fertility decisions too.…”
Section: Discussionsupporting
confidence: 93%
“…Education was also found to be significantly associated with the use of maternal healthcare services and this is consistent with the findings of Furuta and Salway (2006), Sipsma et al (2014), Adeoye (2015), Bhandari et al (2017), Fawole and Tiruneh et al (2017), Duah and Adisah-Atta (2017). This finding can be explained by the Awoleye et al 71 fact that better educated women have access to more information either through the mass media or social media compared to less educated women.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…A study by Pulok et al (2016) based on Bangladesh Demographic and Health Survey found that women from the richest households were about 3 times more likely to have more than four Ante Natal Care visits, delivery at a health facility and skilled attendants at birth compared to women from the poorest households. Bhandari et al (2017) conducted a community-based cross-sectional study for assessing women"s autonomy and utilisation of safe delivery care service in Kapilvastu district of Nepal. The analysis suggested that economic status of household and husband"s education are other dominant predictors of the utilisation of safe delivery care services.…”
Section: Resultsmentioning
confidence: 99%